2010
DOI: 10.4103/1947-489x.211004
|View full text |Cite
|
Sign up to set email alerts
|

Mini-symposium: Ramadan fasting and the medical patient: An overview for clinicians

Abstract: ThedaytimefastingofRamadanisobservedannuallyby millions of adult Muslims all over the world. Some may have mild, moderate or severe medical conditions. They may seek advice on feasibility and safety of fasting and/ ortheirmanagement.Physiciansoughttohaveaworking knowledgeaboutthereligiousrulesofRamadanfastand theirmedicalimplications.Inthisarticlewepresentaconcise summaryoftheproceedingsofaseriesofsymposia.Their objectivesweretoreviewtheeffectsofRamadanfastingon thehealthofMuslimpatientswithvariouschronicmedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 33 publications
(38 reference statements)
0
34
0
Order By: Relevance
“…12 Others noted that under medical supervision fasting was possible for most patients with stable cardiovascular disease without any significant harmful effects. 13,14 Another systemic review and metanalysis revealed that the incidence of cardiac events during fasting was found to be similar to the non-fasting period and Ramadan fast was not related to any increase in the incidence of acute cardiac disease. 15 Similarly, study reported that fasting has no effect on stroke occurrence 16 as well as on number of hospitalization needed for people with cerebrovascular accidents.…”
Section: Discussionmentioning
confidence: 99%
“…12 Others noted that under medical supervision fasting was possible for most patients with stable cardiovascular disease without any significant harmful effects. 13,14 Another systemic review and metanalysis revealed that the incidence of cardiac events during fasting was found to be similar to the non-fasting period and Ramadan fast was not related to any increase in the incidence of acute cardiac disease. 15 Similarly, study reported that fasting has no effect on stroke occurrence 16 as well as on number of hospitalization needed for people with cerebrovascular accidents.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the medical aspects of fasting has increased in the last 30 years [11,12]. In particular, studies on the management of patients with diabetes mellitus have been focused, but the studies focusing on the medical management of thyroid diseases in relation to Ramadan fasting are limited [7,13].…”
Section: Introductionmentioning
confidence: 99%
“…Management of a number of chronic medical conditions in Ramadan has been addressed by Beshyah et al . ( 4 ). In endocrinology, the management of diabetes mellitus has attracted the most attention with the largest volume of literature ( 5 ).…”
Section: Introductionmentioning
confidence: 99%